A spatial dynamics model for heavy-haul electric locomotives considering the dynamic coupling effect of gear transmissions. (October 2019) - He, Chunyan; Chen, Zaigang; Zhai, Wanming; Jiang, Jianzheng; Wang, Kaiyun
A locomotive is usually powered by the electromagnetic torque which is transmitted from the traction motor to the wheelset by gear transmission. In order to investigate the dynamic coupling effects from the gear transmission subsystems on the entire locomotive dynamics system, a comprehensive spatial locomotive dynamics model that considers the dynamic coupling effect of the gear transmissions is developed based on the multibody dynamics theory. In this model, the moved Marker technique is employed to calculate the dynamic mesh force of the gear pairs through which more accurate time-varying gear mesh stiffness excitations could be imported, which is the core of this dynamic model. Then, the established locomotive dynamics model is validated by comparing with the experimental test results. Finally, the dynamic effects of the gear transmissions are revealed by comparing with the results from the traditional locomotive dynamics model without considering the dynamic excitations from the gear transmissions. The results indicate that the gear transmissions have negligible effects on the vibrations of the carbody and the bogie frame, and on the lateral vibrations of the motor and the wheelset. However, the gear transmissions have significant effects on the vertical and, in particular, the longitudinal vibrations of the motor and the wheelset. Thus, it is suggested that the dynamic effects of the gear transmissions are considered in the locomotive dynamics modeling, especially when the vibrations of the motors and the wheelsets are taken into account.